Experimental Research Regarding Rigidity Improvement of Hollow Machine Tools Structures Using Aluminum Foam. (2015) - Simon, Mihai
Abstract: The paper studies a method for improving the static rigidity of hollow critical mechanical structures, without greatly affect its weight. There are many applications for this type of structural parts, where mass is critical and are needed increased rigidity properties. The results are obtained by using alternative technologies and composite materials such as filling the interior hollow spaces with metallic expanded aluminum foam. The study is experimentally implemented to a large HSC (High Speed Cutting) CNC machine tool structural moving part. The benefits obtained by reducing its weight and increasing rigidity properties are: better dynamic performance[1], energy efficiency, mechanical parts less expensive for drive systems[2] .